Pengaruh Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Karyawan Bank Muamalat Purwokerto - Iswari, Zara Devinda; Syarifuddin (eProceedings of Management, 2024)
Bank Muamalat Purwokerto is one of the first banks in Indonesia to operate its business based on Islamic Shariaprinciples. Human resources is a crucial factor in any organization to ensure organizational performance,whether it is non bisnis or institution. People must be managed well to achieve perfomance. Several factorsinfluencing the performance of Bank Muamalat Purwokerto, including organizational culture, organizationalcommitment, and employee performance. The purpose of this study is to analyze the influence of organizationalculture and organizational commitment on the performance of employees of Bank Muamalat Purwokerto. Thisresearch was conducted using quantitative methods, employing descriptive and causal approaches, involving 33respondents. The study utilizize multiple linear regression analysis using through SPSS software version 29. Theresults of the analysis showed that the organizational culture, organizational commitment, and overall employeeperformance were in the good category. Partial hypothesis testing revealed that organizational commitmentsignificantly affects employee performance, while organizational culture does not significantly impact employeeperformance. Organizational culture and organizational commitment collectively account for 66.2% of theinfluence on employee performance, while the remaining 33.8% can be attributed to other variables not discussedin this study.Keywords-organizational culture, organizational commitment, employee performance